Investigação da toxicidade e do mecanismo de ação do aduto de morita-baylis-hillman (CH3ISACN) como um antimalárico - Melo, Cinthia Rodrigues (2024)
Malaria is a disease caused by the bite of the female Anopheles mosquito, which is infected by species of the genus Plasmodium. Although there are different antimalarials, the resistance that parasites have shown to them is a problem, which makes the development of new medicines urgent. Thus, the present work aimed to evaluate the toxicity of repeated doses of the 2-(3-hydroxy-1-methyl-2-oxoindolin-3- yl) acrylonitrile adduct (CH3ISACN), and its ability to reduce parasitemia using the model murine Plasmodium berghei, as well as investigating its mechanism of action as an antimalarial. The subacute toxicological study was based on OECD 407 (2008). CH3ISACN was administered orally to Swiss mice for 28 days at different doses. The animals were distributed into a control group and three treated groups (75 mg/Kg, 150 mg/Kg, 300 mg/Kg). Each group contained 5 males and 5 females. Water consumption, feed, body weight, clinical signs and mortality were analyzed. After 28 days, the animals were euthanized by an overdose of anesthetic, and their blood was collected to evaluate biochemical and hematological parameters, and their organs were collected for histopathological analysis. A genotoxicity study was carried out following OECD 474 (2014). Each group contained three animals: positive control group (50 mg/kg of cyclophosphamide), negative control group (vehicle), group treated 1 and 2 with 300 mg/kg and 600 mg/kg of CH3ISACN respectively. Administration was a single dose by gavage, over 24 hours. For pharmacological evaluation, 5 mice were separated per group. Group 1: test (250 mg/kg of the adduct); Group 2: negative control (vehicle); Group 3: positive control (15 mg of chloroquine); Group 4: organ control. Initially, the animals were inoculated intraperitoneally with erythrocytes infected with P. berghei ANKA, except group 4. They received treatment for 4 consecutive days, and on the 5th/7th day after infection, blood smears were examined to determine parasitemia. Cumulative mortality was observed until the death of one of the animals in group 2. And the animals' organs were subjected to histopathological analysis. The mechanism of action of CH3ISACN as an antiplasmodial agent was investigated based on its ability to inhibit falcipains and/or berghepains. For this, a molecular modeling approach and quantum calculations were carried out, applying docking analysis, molecular dynamics, QM/MM calculations, and MFCC. The toxicological results showed that CH3ISACN did not cause behavioral, physiological or histopathological changes. Also, it did not promote genotoxicity at the doses tested. Thus, the results obtained did not show significant intoxication, ensuring greater safety for its use. CH3ISACN was active against P.berghei, reducing the parasitemia of infected animals by 49.7% and in its histopathological analysis, animals treated by CH3ISACN showed few changes. Its mechanism of action involves the inhibition of FP-2, FP-3, BP-1 and BP-2. Based on the results already obtained, CH3ISACN is promising as a prototype for a new antimalarial. It is important to continue its study, to reach the clinical phase, and thus be part of the therapeutic arsenal against malaria.